Interprofessional Management of Septic Shock: Roles of Pharmacy, Nursing, Dentistry, and Emergency Teams in Early Recognition and Patient Safety - Al-Dossari, Abdullah Shaya Hamad; Mohammed Murdi Abdullah Al-Qahtani; Mohammed Ali Mohammed Al-Sahli; Abdulrahman Saleh Alanazi; Ibrahim Essa Mohammed Essa; Fatimah Mohammed Nasir Alhazmi; Amnah Ahmed Alhazmi; Sharifah Hussain A. Shmakhi; Zahrah Mohammed A. Mahdi; Tahreer Mohammed Naser Hefzy (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Septic shock represents the most severe manifestation of sepsis, characterized by profound circulatory and metabolic dysfunction with high mortality rates. Despite advances in critical care, early recognition and timely intervention remain pivotal for improving outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to delineate the pathophysiology, epidemiology, diagnostic approach, and management strategies for septic shock, emphasizing interprofessional roles in patient safety and early recognition. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of current evidence and clinical guidelines was conducted, integrating epidemiologic data, pathophysiologic mechanisms, and therapeutic protocols from the Surviving Sepsis Campaign. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sepsis incidence continues to rise globally, with mortality rates for septic shock approaching 40–50%. Early identification through vital sign monitoring, laboratory markers (e.g., lactate, WBC), and imaging is critical. Management hinges on rapid initiation of broad-spectrum antibiotics within one hour, aggressive fluid resuscitation, and vasoactive support to maintain mean arterial pressure ≥65 mmHg. Adjunctive therapies such as corticosteroids and vasopressin are reserved for refractory shock. Interprofessional collaboration—nurses for continuous monitoring, pharmacists for antimicrobial stewardship, and proceduralists for source control—significantly improves outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Septic shock remains a life-threatening emergency requiring immediate, coordinated care. Early recognition, timely antimicrobial therapy, and structured resuscitation protocols are essential to reduce mortality and prevent multiorgan failure. Interprofessional teamwork is indispensable for optimizing patient safety and achieving favorable outcomes.